CUSTOMER KNOWLEDGE MANAGEMENT AND MARKET ADAPTATION IN SMALL ENTERPRISES: AN INTEGRATIVE CONCEPTUAL - Raden Roro fatma.sarie85@gmail.com; Maya Ariyanti (Journal of Jabar Economic Society Networking Forum, 2024)
This conceptual paper develops an integrative framework for customer knowledge management and market adaptation in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, it explains how customer insight, knowledge integration, market sensing, service adaptation, and evidence-based decision making can be organized into practical managerial routines. The manuscript does not claim primary survey, interview, experimental, or statistical data. It proposes a staged cycle of diagnosis, capability configuration, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention. The framework emphasizes proportionate implementation and identifies implications for owner-managers, ecosystem institutions, and future empirical research.